Contemporary architectural interventions in the historical tissue of Cádiz – contextual minimalism in the service of genius loci - Białkiewicz, Joanna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
Discussions devoted to the contemporary approach to the historical heritage usually evoke strong emotions, residing somewhere between the conceptual poles of mimetic reproduction and ruthless anastylosis of forms and materials. Against this background, the four projects implemented in Cádiz, Spain, described in this paper appear to be very successful in their somewhat subdued formal character, the emphasis put on functionalism and space revitalisation, and the application of the concept of transparent architecture not conflicting with the historical one, non-aggressive, and at the same time thoroughly modern.